2010
DOI: 10.1097/wnn.0b013e3181df3034
|View full text |Cite
|
Sign up to set email alerts
|

Five-year Survival After Helicobacter pylori Eradication in Alzheimer Disease Patients

Abstract: Hp eradication regimen in AD patients is associated with a higher 5-year survival rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
64
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 98 publications
(72 citation statements)
references
References 0 publications
4
64
0
4
Order By: Relevance
“…This finding further reinforced the possible causal link between H. pylori and AD [12]. In another intervention study with survival as the end point, the group with successful H. pylori eradication compared to those with unsuccessful eradication had significantly lower mortality risk (HR [95% CI] = 0.29 [0.11–0.73]), after adjusting for baseline age and Mini–Mental State Examination score [13]. Looking further into biomarkers of AD, among 53 AD patients, H. pylori infection was associated with lower Mini–Mental State Examination score (P = .024), higher cerebrospinal fluid phosphorylated Tau protein(181) (P = .014), and tau (P = .021) levels [16].…”
Section: Discussionmentioning
confidence: 77%
“…This finding further reinforced the possible causal link between H. pylori and AD [12]. In another intervention study with survival as the end point, the group with successful H. pylori eradication compared to those with unsuccessful eradication had significantly lower mortality risk (HR [95% CI] = 0.29 [0.11–0.73]), after adjusting for baseline age and Mini–Mental State Examination score [13]. Looking further into biomarkers of AD, among 53 AD patients, H. pylori infection was associated with lower Mini–Mental State Examination score (P = .024), higher cerebrospinal fluid phosphorylated Tau protein(181) (P = .014), and tau (P = .021) levels [16].…”
Section: Discussionmentioning
confidence: 77%
“…Таким образом, H. pylori может играть непосредственную роль в развитии ряда дегенеративных заболеваний ЦНС, хотя доказательная база этих находок пока ограничена [7,9]. В небольших исследованиях у пациентов с бо-лезнью Альцгеймера показан положительный эффект эрадика-ции H. pylori, связанный с улучшением когнитивного статуса больных и повышением выживаемости [32,33]. Однако в этом направлении, безусловно, нужны более крупные исследования.…”
Section: терапевтический архив 8 2015unclassified
“…Although minimal hepatic encephalopathy plays a key role in such dysfunction, other factors, such as etiology of cirrhosis, comorbidities, or psychoactive treatments, can also be implicated. [1][2][3] Multiple factors are also involved in the risk of falling. 4 1284 CORRESPONDENCE HEPATOLOGY, March 2013…”
Section: Replymentioning
confidence: 99%
“…[2][3][4] In this respect, we reported that Hp-I is frequently detected in neurodegenerative diseases including CD and Alzheimer's disease (AD) and Hp eradication may positively influence AD manifestations at 2-and 5-year clinical endpoints, 2 thereby supporting a role for this common infection in the pathobiology of the disease. Others also found that AD patients infected by Hp tended to be more cognitively impaired, and patients with dementia have a higher risk of falls and fractures 3 ; Hp-I may also be responsible for osteoporosis.…”
mentioning
confidence: 99%